2017
DOI: 10.1016/j.sleep.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nap paradox: are mid-day sleep bouts a friend or foe?

Abstract: The mid-day nap, sometimes called a siesta, is a ubiquitous occurrence across the lifespan. It is well established that in addition to reducing sleepiness, mid-day naps offer a variety of benefits: memory consolidation, preparation for subsequent learning, executive functioning enhancement, and a boost in emotional stability. These benefits are present even if a sufficient amount of sleep is obtained during the night prior. However, we present a paradox: in spite of these reported benefits of naps, frequent na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 124 publications
4
71
1
Order By: Relevance
“…It should be noted that a nap can provide benefits but also predispose to some situations of risk. The effects described as beneficial are emotional stability and memory consolidation (Mantua & Spencer ). Regarding the harmful effects, cognitive decline, depressive symptoms, cardiovascular and metabolic diseases can be mentioned (Abraham et al, ; Chen et al, ; Cross et al, ; Fang et al, ; Mantua & Spencer ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that a nap can provide benefits but also predispose to some situations of risk. The effects described as beneficial are emotional stability and memory consolidation (Mantua & Spencer ). Regarding the harmful effects, cognitive decline, depressive symptoms, cardiovascular and metabolic diseases can be mentioned (Abraham et al, ; Chen et al, ; Cross et al, ; Fang et al, ; Mantua & Spencer ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects described as beneficial are emotional stability and memory consolidation (Mantua & Spencer ). Regarding the harmful effects, cognitive decline, depressive symptoms, cardiovascular and metabolic diseases can be mentioned (Abraham et al, ; Chen et al, ; Cross et al, ; Fang et al, ; Mantua & Spencer ). It was also verified that there was a greater prevalence of naps among the older adults with four or more health problems, when compared to those who did not report such problems, as well as to those who reported from one–three problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, epidemiological investigations reached controversial conclusions 1 . For instance, some studies have demonstrated that a midday nap could enhance immune system by restoring the neutrophil count to baseline values 2 , reduce the risk of hypertension and metabolic diseases 3 4 and improve alertness, learning capacity and mental health [5][6][7][8][9] , while others found that daytime napping could increase the risks of diabetes mellitus [10][11][12] , hypertension and cardiovascular events 13 14 , obesity 15 and cognitive impairment [16][17][18] . One of the main reasons underlying these contradictory conclusions is the difficulty in determining the causal role of daytime napping in human health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Health effects of siesta are still a debatable issue despite the fact that a number of studies have paid attention to this issue [5]. Studies have utilized two types of designs-crosssectional as well as longitudinal.…”
mentioning
confidence: 99%